Contribuições paleoecológicas para o estudo da paleoparasitologia com base na análise de ossos, osteodermos e coprólitos de vertebrados - Nascimento, Carolina Santa Isabel (2022)
Studies in Paleoparasitology are still scarce worldwide. Interdisciplinary, they can use techniques from different areas of knowledge, such as Paleontology, Archeology, Medicine, Epidemiology, Molecular Biology, Evolutionary Biology and Ecology. The information obtained in paleoparasitological studies concerns not only the organisms and parasitic diseases, but also can provide a lot of information about the paleoenvironment and about the paleoecological relationships involved in the interactions. In this work, different materials from the paleontological collection of the Laboratório de Paleoecologia e Paleoicnologia (LPP), of the Universidade Federal de São Carlos, in São Carlos-SP were analyzed. Such materials were previously collected in other Undergraduate and Postgraduate research at the LPP and taken up again in the present Doctorate because they present some type of evidence of endoparasitism or ectoparasitism. The materials analyzed were coprolites of different vertebrates, from the Northeast region of Brazil, from the archaeological and paleontological site Lagoa Uri de Cima, located in the region of Salgueiro, Pernambuco, collected in a partnership with the Fundação Oswaldo Cruz (Fiocruz do Rio de Janeiro). Dating back to the Pleistocene and Holocene, these materials have not confirmed evidence of parasites. However, nematode larvae, remains of plant (such as pollen grains, starch and phytoliths) and other types of diet were found through macroscopic observation of the diet of the animals, optical microscopy and analysis by computerized microtomography. Another material analyzed was 1300 osteoderms from three individuals of Holmesina Cryptae (Xenarthra, Cingulata, Pampatheriidae), deposited in the LPP collection. This material was obtained after two expeditions, carried out in 2012 and 2014, at Gruta da Lapinha, in the municipality of Iramaia, Bahia. Osteoderms that had marks possibly related to parasitism were observed by optical and scanning electron microscopy. The marks were divided into three types: they could have been caused by fungal infection, being the first description of this type in fossilized osteoderms, by secondary infection, after an initial injury, or by the action of Siphonaptera (fleas), which, therefore, already found in this host at least 20,000 years ago. Finally, the fibula of a sauropod dinosaur from the Upper Cretaceous was also studied, collected in the Northwest of the state of São Paulo and deposited in that collection in 2006. It was recovered by postdoctoral and master researchers in 2017 and 2018, who performed histological analyzes using computed tomography, at the Escola de Medicina da USP and by scanning electron microscopy, at the Universidade do Estado de Campinas, and obtained the result of acute osteomyelitis. In addition, microfossils were found in the vascular channels of the animal, which led to an investigation using optical microscopy at theUniversidade Federal de São Carlos. As a result, about 70 microorganisms were observed preserved inside the vascular channels of the animal, which were described as a possible species of blood parasite, being the first record of parasites inside the bones of these animals. The results of these works and the resulting discussions have been or will be presented in scientific articles, but also in a book, in scientific dissemination events and in locations outside the Universities, with the aim of increasing dialogue and helping to strengthen the approximation between the academic and the external environment research institutes, involving society in general.